2012
DOI: 10.1080/17439760.2012.702784
|View full text |Cite
|
Sign up to set email alerts
|

When the job is a calling: The role of applying one's signature strengths at work

Abstract: Familial aggregation and the effect of parenting styles on three dispositions toward ridicule and being laughed at were tested. Nearly 100 families (parents, their adult children, and their siblings) completed subjective questionnaires to assess the presence of gelotophobia (the fear of being laughed at), gelotophilia (the joy of being laughed at), and katagelasticism (the joy of laughing at others). A positive relationship between fear of being laughed at in children and their parents was found. Results for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(123 citation statements)
references
References 39 publications
2
118
0
3
Order By: Relevance
“…Fredrickson, 2001;Seligman & Csikszentmihalyi, 2000) and positive occupational health psychology (cf. Bakker & Derks, 2010), individual-level interventions strengthen the awareness and competency of proactively building a resourceful environment and applying one's strengths and virtues to enhance positive well-being and health-see for example the self-tuning approach in this chapter (Vinje, 2007), the values in action (VIA) (Harzer & Ruch, 2012;Peterson & Seligman, 2004), job crafting (Tims & Bakker, 2010;Wrzesniewski & Dutton, 2001), psychological capital development (Luthans, Avey, Avolio, Norman, & Combs, 2006), mindfulness training (Hülsheger, Alberts, Feinholdt, & Lang, 2013), and positive psychology at work in general (Bono, Glomb, Shen, Kim, & Koch, 2013;Mills, Fleck, & Kozikowski, 2013).…”
Section: Making Salutogenesis Visiblementioning
confidence: 99%
“…Fredrickson, 2001;Seligman & Csikszentmihalyi, 2000) and positive occupational health psychology (cf. Bakker & Derks, 2010), individual-level interventions strengthen the awareness and competency of proactively building a resourceful environment and applying one's strengths and virtues to enhance positive well-being and health-see for example the self-tuning approach in this chapter (Vinje, 2007), the values in action (VIA) (Harzer & Ruch, 2012;Peterson & Seligman, 2004), job crafting (Tims & Bakker, 2010;Wrzesniewski & Dutton, 2001), psychological capital development (Luthans, Avey, Avolio, Norman, & Combs, 2006), mindfulness training (Hülsheger, Alberts, Feinholdt, & Lang, 2013), and positive psychology at work in general (Bono, Glomb, Shen, Kim, & Koch, 2013;Mills, Fleck, & Kozikowski, 2013).…”
Section: Making Salutogenesis Visiblementioning
confidence: 99%
“…This movement fuelled various other research studies on the application and use of strengths within the workplace and, subsequently, positive organisational outcomes have been attributed to the strengths approach. Various studies have shown that work engagement is one of the positive outcomes of the use of strengths (Botha & Mostert, 2014;Harter, Schidt & Hayes, 2002;Harzer & Ruch, 2012Keenan & Mostert, 2013;Stander, Mostert & De Beer, 2014;Van Woerkom, Oerlemans & Bakker, 2015). In addition, Clifton and Harter (2003) have indicated that productivity increases for employees who use their strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that strengths use is related to higher levels of self-efficacy (Falender & Shafranske, 2004;Van Woerkom, Oerlemans & Bakker, 2015b), increased happiness and vitality (Govindji & Linley, 2007), subjective well-being (Proctor, Maltby & Linley, 2011), increased work engagement (Harzer & Ruch, 2012, 2013, goal attainment (Linley, Nielsen, Wood, Gillett & Biswas-Diener, 2010), increased in-role and out-role performance and lower levels of sick leave (Van Woerkom, Bakker & Nishii, 2015a). Recently, however, some scholars have objected that the positive psychology movement has again created an imbalance by focusing almost exclusively on employee strengths while failing to pay an equal amount of attention to employee deficits (Rust, Diessner & Reade, 2009;Sirmon, Hitt, Arregle & Campbell, 2010).…”
Section: Introductionmentioning
confidence: 99%